Low-income consumers’ disposition to use automated banking services (2022)
Automated banking services rely on the so-called fintech technologies. These technologies, however, represent an opportunity to enhance financial inclusion indicators among low-income customers. This paper aims to develop a new conceptual framework to analyse low-income consumers’ disposition to use automated banking services. The work consists of an omnibus study conducted in eight major cities of Colombia. A survey aiming to measure the disposition to use automated banking services as a function of technology disposition provided by bank firms was developed and validated with a sample of 483 Colombian low-income residents. An exploratory analysis was applied, estimating items variance and co-variance matrices. Sampling adequacy and assumption evaluation were evaluated through the Kaiser-Meyer-Olkin test, Tau-equivalence test, and homogeneous items test. Robust parameters were estimated via Structural Equation Modelling following the standards of reproducible research. Statistical, robust, and significant relationships between technology disposition and use of automated banking services in low-income Colombian consumers were confirmed, suggesting the potential success of deploying these services as a means to boost financial inclusion in this segment. This study provides fresh conceptual insights on low-income customers’ disposition to adopt and use ever-changing technologies for the financial and banking sector. It is among the first empirical studies that provide empirical evidence that breaks the stereotype that low-income customers are reluctant to use new technologies in the financial sector.